Educating Students About Autism Spectrum Disorder Using the Kit for Kids Curriculum: Effects on Knowledge and Attitudes. Issue 2 (1st June 2019) - Campbell, Jonathan M.; Caldwell, Elizabeth A.; Railey, Kirsten S.; Lochner, Olivia; Jacob, Rachel; Kerwin, Shelby
Abstract: Elementary school students frequently report no knowledge about autism spectrum disorder (ASD) and often endorse negative attitudes toward peers with ASD. Investigators evaluated a peer education autism program, the Kit for Kids (KfK), with 234 students from 19 classrooms and 3 elementary schools. Students receiving the KfK curriculum reported greater autism knowledge when compared to controls (i.e., Time 1) and maintained knowledge at the 1-week follow up. Controls received KfK 1 week later and reported significant gains in knowledge. For students unfamiliar with autism, KfK improved initial attitudes toward autism when compared to controls. At Time 2, intervention and control attitudes were similar, suggesting that the initial effect of KfK for naïve students persisted over 1 week. Gender was a robust predictor of attitudes, with girls reporting more favorable attitudes compared to boys. Recommendations for additional research and use of peer education and autism awareness efforts within schools are offered.